Spectrophotometric studies of asteroids ii: taxonomic type - Aimanova, G.K.; Serebryanskiy, A.V.; Shcherbina, M.P.; Krugov, M.A. (Karagandy University of the name of academician E.A. Buketov, 2025)
Analysis of spectral observations of a number of Main Belt asteroids, the Apollo family asteroid (NEO) 30825 (1990 TG1), and the rare asteroid 1951 Lick was used to determine their taxonomic types. The observations were carried out in 2023-2024 at the Assy-Turgen Observatory on the AZT-20 telescope equipped with a spectrograph using a volume-phase holographic dispersive element with 360 lines per millimeter in lowresolution mode (R=600). We use the “template” method proposed in (Savelova A.A. et al., 2022) and the visual albedo values. An analysis was carried out for S-type asteroids (107) Arachne and (482) Petrina and the Apollo family asteroid (NEO) 30825 (1990 TG1), which have minerals formed under high-temperature conditions, as well as asteroid (97) Klotho, belonging to the M class, which includes asteroids with an increased metal content. Class A asteroids are characterized by high albedo and a marked increase in reflectance at longer wavelengths. These features indicate the presence of high-temperature olivine or mixtures of olivine with metals, mainly iron and nickel. The presented results show that asteroids (366) Vincentina and (1951) Lick belong to this class. The analysis showed that the normalized reflectance spectrum of (47) Aglaja corresponds to asteroids of spectral class B, the main components of the surface of which are probably anhydrous silicates, hydrated clay minerals, organic polymers, magnetite, and sulfides. According to the authors' results, the normalized reflectance spectrum of asteroid (718) Erida corresponds to the spectral corridor for the T-class template with an albedo ranging from 0.04 to 0.042.
Keywords: spectrophotometry; asteroids; taxonomic type; reflective spectroscopy